Physical layer security of NOMA-D2D cooperative wireless system - Yifan DING; Guangqiu LI; Hui LI (Dianxin kexue)
Aiming at the physical layer security (PLS) application requirement of massive user equipments access in the future, the PLS model combining with non-orthogonal multiple access (NOMA), device-to-device (D2D) and relay cooperation was proposed.The model was composed of base station with transmit antenna selection (TAS), NOMA far cellular user of base station and D2D transmitter, D2D receiver and passive eavesdropper, the D2D transmitter was also assumed two roles of NOMA near user of base station and decode-and-forward relay.The approximate expressions for the secrecy outage probability, non-zero secrecy capacity probability and asymptotic secrecy outage probability of NOMA-D2D cooperative wireless system under two TAS schemes were derived by using Gaussian-Chebyshev Quadrature theorem.Numerical and simulation results verify the accuracy of PLS performance analysis of NOMA-D2D cooperative wireless system.The results also show that increasing the power allocated to far cellular user under constant total power of base station can effectively improve PLS performance of NOMA-D2D cooperative wireless system.